2015
DOI: 10.1128/genomea.01297-15
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Member of Chitinophagaceae Isolated from a Human Peritoneal Tumor

Abstract: Peritoneal tumors from a rare malignancy, pseudomyxoma peritonei, frequently contain bacteria. Evidence suggests that tumor-associated bacteria contribute to pseudomyxoma peritonei development and/or progression. One unique isolate (PMP191F) was characterized via whole-genome sequencing using the Illumina MiSeq platform. PMP191F shows similarities to the Chitinophaga, Niastella, and Flavitalea genera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Subsequent whole-genome sequencing revealed that PMP191F closely resembled Niastella, Chitinophaga, and Flavitalea genera with a definite identity. It was hypothesized that this isolate represents a novel bacteria species that might bind MUC2 and potentially influence PMP progression [21]. However, as this is based on a single isolate, it naturally requires further validation and deeper analysis.…”
Section: Bacteria and Pmpmentioning
confidence: 99%
“…Subsequent whole-genome sequencing revealed that PMP191F closely resembled Niastella, Chitinophaga, and Flavitalea genera with a definite identity. It was hypothesized that this isolate represents a novel bacteria species that might bind MUC2 and potentially influence PMP progression [21]. However, as this is based on a single isolate, it naturally requires further validation and deeper analysis.…”
Section: Bacteria and Pmpmentioning
confidence: 99%
“…Chitinophagaceae (phylum Bacteroidetes) comprises a ubiquitous bacterial family that was recently described in soil (Bailey, Fansler, Stegen, & McCue, 2013;Lv, Wang, Chen, You, & Qiu, 2016), freshwater (Leite et al, 2016;Siddiqi & Im, 2016), a hypersaline lake (Vavourakis et al, 2016), hot springs (Hanada, Tamaki, Nakamura, & Kamagata, 2014), maize roots (Gao et al, 2016) and human tumours (Lo et al, 2015). This is a clade with strong taxonomic support, even though few genomes have been fully sequenced to date.…”
Section: Introductionmentioning
confidence: 99%
“… Niastella has been isolated from soil, and there are few studies regarding the role of Niastella in disease. A unique microorganism named PMP191F, with similarities to Niastella , has been isolated from peritoneal tumours [38, 39]. The genus Actinosynnema is a culture source of ansamitocin P-3 against tumours [40].…”
Section: Discussionmentioning
confidence: 99%